ANALISIS PEUBAH KONSUMSI PANGAN DAN SOSIAL EKONOMI UNTUK MENENTUKAN INDIKATOR KELAPARAN - abu bakar (Jurnal Sosial Humaniora, 2011)
Aim of the study was to analyze food consumption and socio-economic parameters in order for determine starvation indicators. The study was designed in a cross sectional method and samples collected in gradual cluster. First cluster consisted of four sub districts with eight selected-villages and as many as 233 samples were withdrawn from the eight villages for analyzing in discrimination method. If rice were used as starvation indicator, 48.5% of samples suffered starvation. The study resulted that 85% of the samples ate twice daily while 15% of the samples ate three times in a day. According to frequency of food consumption as starvation indicator, the samples did not suffer from starvation. In addition, the study showed that 45.8% samples of city areas which the member more than four people suffered starvation and so did the 68.1% samples lived in villages which the member more than four people. Moreover, 15% of husband which bachelor degree holders lived in city areas and 1.8% of husband which bachelor degree holders lived in villages did not suffer from starvation. As many as 45% of heads of families whose work as government employees at city areas and 2.7% of heads of families whose work as government employees at villages did not suffered from starvation. Based on food expenses criteria used as a starvation indicator, 32.5% samples lived at city areas and 83.2% samples lived at villages were suffer from starvation. The study showed that high sensitivity at either cities or villages occurred on bachelor degree holders and government employee’s criteria, and contrary, the high specificity at either cities or villages occurred on government employee’s criteria when food expenses criteria used as a gold standard